(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article about the nature and types of the parable genre. The fable easily connects with other genres of literature, deepening their meaning. The fabledevelops logic and imaginative thinking, forms moral values and gives ideas about life.